Corporate Governance and Audit Quality in Islamic Banks in Emerging Asian Economies: A Literature Review - Chohan, Aiman Hussain; Ul Haq, Ayaz (Journal of Development and Social Sciences, 2025)
This systematic literature review explores the relationship between corporate governance and audit quality in Islamic banks within emerging Asian economies. It focuses on how governance systems like board independence, audit committee effectiveness, and Shariah supervisory boards influence audit reliability and stakeholder confidence. Islamic banks present a unique challenge as they integrate conventional corporate governance with Shariah principles. The review synthesizes peer-reviewed literature from 2010 to 2025, drawing on agency, stakeholder, institutional, and resource dependency theories. Findings indicate that while governance structures aligned with ethical and religious oversight improve audit quality, inconsistencies in regulatory frameworks and varying institutional capacities across countries serve as critical moderators. A notable gap is observed in empirical research regarding the impact of Shariah supervisory boards on audit quality and the lack of standardized audit quality metrics. The study recommends further empirical research on the role of Shariah boards and standardized audit measures, alongside practical steps to harmonize governance frameworks and enhance institutional capacity.